2023
DOI: 10.3390/biomedicines11102597
|View full text |Cite
|
Sign up to set email alerts
|

Mometasone Furoate Inhibits the Progression of Head and Neck Squamous Cell Carcinoma via Regulating Protein Tyrosine Phosphatase Non-Receptor Type 11

Lin Qiu,
Qian Gao,
Anqi Tao
et al.

Abstract: Mometasone furoate (MF) is a kind of glucocorticoid with extensive pharmacological actions, including inhibiting tumor progression; however, the role of MF in head and neck squamous cell carcinoma (HNSCC) is still unclear. This study aimed to evaluate the inhibitory effect of MF against HNSCC and investigate its underlying mechanisms. Cell viability, colony formation, cell cycle and cell apoptosis were analyzed to explore the effect of MF on HNSCC cells. A xenograft study model was used to investigate the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Therefore, non-invasive biomarkers such as tumor oxygenation and signals from autofluorescence imaging, intensity signals from optical coherence tomography, and ultrasound wave signals from surface tumor tissues have been shown to provide accurate predictions for early detection and prognosis assessments in OSCC [30]. To overcome these challenges, this Special Issue has accepted a few publications that highlighted the potential biomarkers that can be used for diagnostic and therapeutic purposes [31][32][33][34][35][36][37][38][39][40]. The diagnostic section can be divided into biomarkers for OSCC and prognosis.…”
Section: Limitations Challenges and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, non-invasive biomarkers such as tumor oxygenation and signals from autofluorescence imaging, intensity signals from optical coherence tomography, and ultrasound wave signals from surface tumor tissues have been shown to provide accurate predictions for early detection and prognosis assessments in OSCC [30]. To overcome these challenges, this Special Issue has accepted a few publications that highlighted the potential biomarkers that can be used for diagnostic and therapeutic purposes [31][32][33][34][35][36][37][38][39][40]. The diagnostic section can be divided into biomarkers for OSCC and prognosis.…”
Section: Limitations Challenges and Conclusionmentioning
confidence: 99%
“…This Special Issue also published a comprehensive review that provides an update on recent studies using preclinical models of HNSCC to investigate the role of natural products as therapeutic or chemo preventive agents to improve patient clinical outcomes [39]. In addition to the potential of natural products as therapeutic agents for HNSCC, this Special Issue also published an original article highlighting the role of mometasone furoate (MF) as a potential therapeutic agent targeting PTPN11, which halts tumorigenesis in vitro and impairs tumor growth in vivo using a preclinical model of HNSCC [31]. For the diagnostic approach that focuses on the early detection in OSCC, Surendran et al [37] demonstrated the gradual increments in the infiltration of Tregs (CD4, CD25, FOXP3), exhausted CD8 T cells (CD8 and PD-1) in the immune microenvironment, and the expression of PD-L1 in epithelial cells in the oral carcinogenesis mechanism, from normal epithelium to dysplasia and eventually to invasive SCC.…”
Section: Limitations Challenges and Conclusionmentioning
confidence: 99%